2001
DOI: 10.1021/jf010713g
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of a Quercetin Metabolite, Quercetin 3-O-β-d-Glucuronide, on Lipid Peroxidation in Liposomal Membranes

Abstract: To study the antioxidant activity of quercetin 3-O-beta-D-glucuronide (Q3GA), which is one of the quercetin metabolites in the blood after intake of quercetin-rich food, the inhibitory effect of Q3GA on lipid peroxidation was estimated using phosphatidylcholine large unilamellar vesicles (PC LUV) as a biomembrane model. Iron ion, an aqueous peroxyl radical generator, a peroxynitrite generator, or lipoxygenase was used as the inducer of lipid peroxidation. In all cases, Q3GA inhibited lipid peroxidation signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…Circulating metabolites of flavonoids, such as glucuronides, sulphates and conjugated O-methylated forms, or intracellular metabolites like flavonoid-GSH adducts, have significantly reduced antioxidant potential relative to the forms found in plants [102]. Indeed, studies have indicated that although such conjugates and metabolites may participate antioxidant reactions and may scavenge reactive oxygen and nitrogen species in the circulation, their effectiveness to do so is reduced compared to their parent aglycones [22,70,94,117,132].…”
Section: Absorption Metabolism and Distribution Of Flavonoidsmentioning
confidence: 99%
“…Circulating metabolites of flavonoids, such as glucuronides, sulphates and conjugated O-methylated forms, or intracellular metabolites like flavonoid-GSH adducts, have significantly reduced antioxidant potential relative to the forms found in plants [102]. Indeed, studies have indicated that although such conjugates and metabolites may participate antioxidant reactions and may scavenge reactive oxygen and nitrogen species in the circulation, their effectiveness to do so is reduced compared to their parent aglycones [22,70,94,117,132].…”
Section: Absorption Metabolism and Distribution Of Flavonoidsmentioning
confidence: 99%
“…Circulating metabolites of flavonoids, such as glucuronides, sulphates and conjugated O-methylated forms, or intracellular metabolites like flavonoid-GSH adducts, have greatly reduced antioxidant potential [160]. Indeed, studies have indicated that although such conjugates and metabolites may participate directly in plasma antioxidant reactions and in scavenging reactive oxygen and nitrogen species in the circulation, their effectiveness is reduced relative to their parent aglycones [41,122,152,170,189].…”
Section: Flavonoid Metabolism and Access To The Brainmentioning
confidence: 99%
“…Considering the present results with baicalein and baicalin, the lower activity observed in baicalin suggested that a disappearance of 7-hydroxyl group by glucosylation weakened the radical-scavenging power of the compound. Shirai et al (2001) reported that the introduction of a glucuronide group to the 3-position contributed to an increase of affinity toward lipid, resulting decrease of the antioxidative activity. The effect of glucosylation of hydroxyl group at 7-position on affinity toward lipid was studied by van Dijk et al (2000), and it was shown that the glucosylation at 7-position resulted in increase of affinity.…”
Section: Lipid Peroxidation Inhibition Activities Of Flavonoidsmentioning
confidence: 99%